Litofácies e relações estratigráficas da formação Aquidauana no nordeste da Bacia do Paraná - São Sebastião do Paraíso (MG) - Ferreira, Gustavo Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The Aquidauana Formation is characterized by sandstones of variable granulation, mudstones and diamectites abundant in clay, typical colors like brick red (vermelho tijolo) of glacial, fluvial and lacustrine origin. It’s chronostratigraphic equivalent to the Itarará group from the Neo Carboniferous age, that under the exploratory view, such units represent important intervals in the basin, occurring together with them minerals as well as energy resources as petroleum, underground water and coal – what requires a great paleogeography and stratigraphy knowledge for its exploration. By gathering information from the columnar sections of the area, it was possible to characterize the sedimentary facies, the stacking pattern as well as the association. It was also made an attempt of stratigraphic correlation, which showed great difficulties since glacial environments present a great lateral discontinuity of the facies besides the complex relationship process of formation. As a result, it was obtained 8 sedimentary facies, the lateral and vertical relations and genesis process. It is proposed that the sedimentary environment in the study area is the fluvio glacial, characterized by alluvial systems formed by defrosted water which transport the sediments that are deposited in plains in front of the glacier (distal outwash). Petrographic thin section analysis showed that the transportation process was ineffective. The grains present punctual to lobular contacts, characterizing good porosity and permeability to the rock, varying these qualities according to more or less existence of matrix. The presence of Iron Oxide deposited between the recrystallization border and feldspathic mineral indicates that this rock has possibly presented a primary rubefaction, intensified by alkaline fluid percolation

A Formação Aquidauana é caracterizada por arenitos de granulação variável, lamitos e diamictitos com abundância de material argiloso, cores típicas vermelho tijolo, de origem glacial, fluvial e lacustre. É equivalente cronoestratigráfica do Grupo Itararé, de idade neocarbonífero, que sob o ponto de vista exploratório, tais unidades representam importantes intervalos da bacia, tendo associadas a elas diversas ocorrências de bens minerais e recursos energéticos como petróleo, água subterrânea, carvão, sendo necessários para a prospecção e explotação desses recursos um bom entendimento da estratigrafia e paleogeografia. Com o levantamento de seções colunares representativas da área foi possível caracterizar as fácies sedimentares, seu empilhamento e associação. Foi realizada ainda uma tentativa de correlação estratigráfica que apresentou grande dificuldade uma vez que ambientes glaciais exibem grande descontinuidade lateral das fácies além da complexa relação dos processos geradores. Como resultado foram obtidas oito fácies sedimentares, suas relações verticais e laterais, e seus processos geradores. Propõe-se que o ambiente de sedimentação na área de estudo é o flúvio-glacial, caracterizado por sistemas aluviais formados por água de degelo que transportam os sedimentos que se depositam em planícies na frente da geleira (outwash distal). Análises petrográfica de lâminas delgadas mostraram que o processo de transporte era ineficiente. Os grãos possuem contatos pontuais a lobulares caracterizando uma boa porosidade e permeabilidade a rocha, variando estas qualidades em função da maior ou menor presença de matriz. A presença de óxido de ferro depositada entre a borda de recristalização e o mineral feldspático indica que possivelmente essa rocha já apresentava uma rubefação primária, intensificada pela percolação de fluido alcalino
Keywords: Geologia estratigráfica; Parana, Rio, Bacia; Facies (Geologia); Geologia estratrigráfica - Holoceno; São Sebastião do Paraíso (MG); Geology, Stratigraphic; Facies (Geology); Geology, Stratigraphic Holocene